Cannabidiol for treating drug‐resistant epilepsy in children: the New South Wales experience. Issue 5 (13th August 2018) - Chen, Kerrie‐Anne; Farrar, Michelle; Cardamone, Michael; Gill, Deepak; Smith, Robert; Cowell, Christopher T; Truong, Linda; Lawson, John A
Abstract: Objective: To evaluate the tolerability and safety of cannabidiol for treating drug‐resistant epilepsy in children, and to describe adverse events associated with such treatment. Study design: Prospective, open label cohort study. Setting: Three tertiary NSW referral centres with paediatric neurology services. Participants: First 40 children enrolled in the NSW Compassionate Access Scheme for children with drug‐resistant epilepsy and uncountable daily seizures. Intervention: Children received cannabidiol as an adjunct anti‐epileptic drug, titrated to a maximum of 25 mg/kg/day, for up to 12 weeks. Outcome measures: Adverse events, withdrawals, and caregiver and physician Global Impression of Change assessments were recorded at 4, 8 and 12 weeks. Seizure frequency could not be reliably recorded because of disease severity. Results: Thirty‐nine patients reported at least one adverse event; many were deemed unrelated to cannabidiol treatment. The most frequent treatment‐related adverse event was somnolence (15 participants), which resolved spontaneously in ten patients; it was particularly frequent in patients taking higher clobazam doses. Gastrointestinal effects (nausea, vomiting, diarrhoea) were each reported by seven to nine participants. Four children were withdrawn from treatment, including one with elevated transaminase levels. The caregivers of 12 children felt the overall health of their children had much or very much improved; clinicians assessed seven children as being much or very much improved. Conclusion: Cannabidiol as an adjunct treatment had some subjective benefit for overall health, with a manageable adverse event profile. Monitoring changes in liver function and awareness of potential drug interactions is essential. Whether the reported benefit is attributable to cannabidiol cannot be established in an open label study of participants with severe intractable epilepsy.